Good Corporate Governance's Impact on Sustainability Reporting Disclosure - Sari Mujiani; Stya Sri Rohmawati (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
The goal of this study is to see how good corporate governance affects the disclosure of sustainability reports in mining companies listed on the Indonesia Stock Exchange between 2017 and 2020, with profitability as a moderating factor. The population of this study includes all mining companies operating between 2017 and 2020. Samples were collected using a purposive sampling strategy with specific criteria during the research period. Based on the criteria defined using panel data, the maximum amount of data that can be processed is 40 data points. The analysis, which is done with Eviews 12, uses panel data regression and moderated regression analysis. According to the study's findings, (1) the board of directors has a positive and significant impact on the disclosure of the sustainability report. (2) The Audit Committee has a positive and significant impact on the disclosure of the sustainability report.